Child care and the welfare to work transition - Robert J. Lemke; Robert Witt; Ann Dryden Witte (Wellesley College, Department of Economics, 2001)
We assess the role of child care in the welfare to work transition using an unusually large and comprehensive data base. Our data are for Massachusetts, a state that began welfare reform in 1995 under a federal waiver, for the period July 1996 through August 1997. We find that both the nature of the child care market and the availability and policies of subsidized care and early education affect the probability that current and former welfare recipients will work. Regarding the child care market, we find that the availability of care is most consistently related to employment. However, the price and quality of care also matter. We also find that increased funding for child care subsidies, and the availability of full day kindergarten and Head Start significantly increase the probability that current and former welfare recipients work. Higher state payments to providers are associated with increased probabilities of work. Finally, recipients are more likely to work when they are subject to a work requirement. The effects of imposing time limits on cash assistance are less clear.
Keywords: I38; J22; H40; I20; 330; Child Care; Welfare Reform; Vouchers; Labor Supply; Time Limits; Kinderbetreuung; Familienleistungsausgleich; Arbeitsangebot; Mütter; USA